2021
DOI: 10.1371/journal.pone.0253665
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use and challenges of implementing virtual visits during COVID-19 in primary care and lessons for sustained use

Abstract: Background The COVID-19 pandemic has rapidly transformed how healthcare is delivered to limit the transmission of the virus. This descriptive cross-sectional study explored the current use of virtual visits in providing care among primary care providers in southwestern Ontario during the first wave of the COVID-19 pandemic and the anticipated level of utilization post-pandemic. It also explored clinicians’ perceptions of the available support tools and resources and challenges to incorporating virtual visits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 20 publications
2
115
0
7
Order By: Relevance
“…Nomenclatures regarding remote care strategies varied considerably among studies, with the terms “telehealth” [ 30 , 33 , 36 , 44 , 45 , 47 , 54 , 55 , 60 , 63 , 64 , 67 - 69 , 72 ] and “telemedicine” [ 29 , 31 , 32 , 38 , 39 , 46 , 47 , 51 , 59 , 61 , 63 , 69 , 71 ] being the most frequent. The following terms were also mentioned: teleconsultation [ 40 , 58 , 71 ], virtual visit [ 41 , 48 , 58 ], virtual health/eHealth [ 35 , 51 ], remote consultation [ 37 , 50 , 56 , 65 ], electronic consultation [ 35 , 62 ], telephone follow-up [ 35 , 66 ], video visit [ 35 , 70 ], video consultation [ 34 , 49 ], online consultation [ 69 ], virtual care [ 53 ], web-based video consultation [ 69 ], digital monitoring [ 72 ], nonpresential consultation [ 52 ], and remote self-monitoring [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nomenclatures regarding remote care strategies varied considerably among studies, with the terms “telehealth” [ 30 , 33 , 36 , 44 , 45 , 47 , 54 , 55 , 60 , 63 , 64 , 67 - 69 , 72 ] and “telemedicine” [ 29 , 31 , 32 , 38 , 39 , 46 , 47 , 51 , 59 , 61 , 63 , 69 , 71 ] being the most frequent. The following terms were also mentioned: teleconsultation [ 40 , 58 , 71 ], virtual visit [ 41 , 48 , 58 ], virtual health/eHealth [ 35 , 51 ], remote consultation [ 37 , 50 , 56 , 65 ], electronic consultation [ 35 , 62 ], telephone follow-up [ 35 , 66 ], video visit [ 35 , 70 ], video consultation [ 34 , 49 ], online consultation [ 69 ], virtual care [ 53 ], web-based video consultation [ 69 ], digital monitoring [ 72 ], nonpresential consultation [ 52 ], and remote self-monitoring [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Virtual visits sometimes face technical challenges that diminish the quality of the interaction and may have a high no‐show rate. For low‐income families, the purchase of required equipment may represent an excessive financial burden 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with Brant et al [ 37 ], who found that the majority of practices in 5 areas of the United Kingdom conducted telephone consultation, while none provided video consultation. In addition, Heba and colleagues [ 38 ] reported that during COVID-19, 96.6% of general practitioners in southwestern Ontario used teleconsultation, but 99.5% of this was conducted via telephone consultation. A study looking at telehealth implementation in Australia showed that even with a change in reimbursement policy in the country, Australian health care providers, especially primary care providers, still preferred telephone consultation over video consultation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%